Research of Degradation Processes of Insulator Porcelain C 130 Type - RANACHOWSKI, Przemysław; REJMUND, Feliks; RANACHOWSKI, Zbigniew; PAWEŁEK, Andrzej; PIĄTKOWSKI, Andrzej (Archives of Acoustics, 2008)
This paper presents the results of acoustic emission (AE) measurements of samples under compressive stress. Additional research, concerning structure and parameters of the material, was performed using microscopic and ultrasonic methods. The object of the investigation were samples of porcelain material C 130 type of domestic long-rod insulator LP 75/31W. This kind of aluminous porcelain demonstrates high mechanical and electrical strength as well as resistance to aging degradation processes. It finds wide application in modern electrotechnical engineering. The aim of this study was to recognize stages of degradation processes of the porcelain structure. The present work constitutes a continuation of the study concerning the influence of technological faults, existing in porcelain material structure, on long-term mechanical strength. These results were presented at the OSA Conference in 2006. The analysis of mechanical-acoustic characteristics pointed out diversified strength and complicated mechanism of the material degradation. The effectiveness of the dispersive and fibrous reinforcement of aluminous porcelain C 130 type was ascertained. It was stated during the microscopic investigation that the structure of the material is different from that in the case of typical aluminosilicate ceramic materials. The main reason for this effect is due to densely dispersed corundum and mullite fine crystals in glassy matrix.